2017
DOI: 10.1002/bio.3375
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, density functional theory calculations and luminescence of lanthanide complexes with 2,6‐bis[(3‐methoxybenzylidene)hydrazinocarbonyl] pyridine Schiff base ligand

Abstract: A pyridine-diacylhydrazone Schiff base ligand, L = 2,6-bis [(3-methoxy benzylidene) hydrazinocarbonyl]pyridine was prepared and characterized by single crystal X-ray diffraction. homogeneous and heterogeneous catalysis. [16][17][18] Following our recently published work towards the complexation of lanthanide(III) nitrate salts with dimethyl pyridine-2,6-dicarboxylate, we were interested in the synthesis of a 2,6-bis [(3-methoxybenzylidene)hydrazine carbonyl]pyridine L ligand derived from dimethyl pyridine-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 41 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…This highest activity may be related to the fact that Dy (III) has the highest positively charged density because it has the smallest size in the series. It can quench the DPPH radical more efficiently than the other lanthanide ions …”
Section: Resultsmentioning
confidence: 99%
“…This highest activity may be related to the fact that Dy (III) has the highest positively charged density because it has the smallest size in the series. It can quench the DPPH radical more efficiently than the other lanthanide ions …”
Section: Resultsmentioning
confidence: 99%
“…Due to the importance that Schiff base derivatives possess, several Schiff‐base units and their corresponding metal complexes were synthesized and thermodynamically studied 30 . These findings highlight the broad spectrum of therapeutic possibilities offered by Schiff bases, driving continued interest and investigation into their pharmacological potential 31,32 . Schiff bases that contain additional electron‐donating groups, such as N, O, and S are playing a crucial role in metallo‐biomolecules 10 .…”
Section: Introductionmentioning
confidence: 99%
“…30 These findings highlight the broad spectrum of therapeutic possibilities offered by Schiff bases, driving continued interest and investigation into their pharmacological potential. 31,32 Schiff bases that contain additional electron-donating groups, such as N, O, and S are playing a crucial role in metallo-biomolecules. 10 It has been found that the coordination of Schiff base ligands through heteroatoms with lanthanide ions or transition metals enhances the biological activity 33,34 as well as the optical properties of these ligands, which has been attributed to the ion pairs on these atoms.…”
Section: Introductionmentioning
confidence: 99%
“…In continuation of our research on synthesis of Schiff base ligands and their lanthanide complexes [29][30][31][32][33][34], herein we have focused on synthesis, characterization and luminescent properties of a series of lanthanide complexes with H 2 L ligand. Their biological activity has been tested against some clinical important bacteria.…”
Section: Introductionmentioning
confidence: 99%